PEMBUATAN PAPAN ABSENSI UNTUK MENINGKATKAN DISIPLIN WAKTU PADA SISWA KELAS 3 C MIS ALMOURQY - Mupia Mupia; Rahtya Ananta; Sri Nora Aulia; Ghustyan Ghema Ramadhan; Abdul Rahmat (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The purpose of this study was to determine the extent to which classroom management can improve discipline-friendly attitudes in class 3 C MIS Almourqy. Purposive sampling is a qualitative research technique used in this study. Purposive sampling often selects informants who are familiar with the problem being studied. Class 3 C students and teachers at MIS Almourqy were used as research samples. Based on research findings, classroom management can improve the discipline attitude of class 3 C students at MIS Almourqy.